The Effect of Price Perceptions and Purchase Intention on Purchase Decisions of Fashion Products Through the Marketplace Shopee in Students of Walisongo State Islamic University: Pengaruh Persepsi Harga dan Minat Beli terhadap Keputusan Pembelian Produk Fashion melalui Marketplace Shopee pada Mahasiswa Universitas Islam Negeri Walisongo Semarang - Fahriza, Talita; Madita, Rach; Islami, Elvina Rachel Putri; Nafiah, Muhimatun; Fahmy, Zulfa; Zikrinawati, Khairani (Journal of Multidisciplinary Science, 2023)
Fashion needs are still a product that is favored by all groups, especially students. In this digital era, Shopee is one of the marketplaces that provides various types of fashion products and encourages people to tend to make purchasing decisions online. Purchasing decisions from consumers on a marketplace are influenced by many factors, ranging from price perceptions by consumers, purchase interest, brand ambassadors, advertisements, marketplace appearance, service quality, and many more. This study aims to measure the effect of price perception and purchase interest on purchasing decisions for fashion products through the Shopee marketplace for students of Walisongo State Islamic University Semarang. This research was conducted using linear regression data analysis techniques and using a quantitative approach through purposive sampling techniques with a sample of 100 respondents. Based on the results of the analysis, it can be stated that price perception and purchase intention simultaneously influence the decision to purchase fashion products with an F-count value of 49.757 with sig <0.001. The results of this study indicate that price perceptions and purchase intention have a partially significant positive effect on purchasing decisions for fashion products through the Shopee marketplace for UIN Walisongo Semarang students, so it can be concluded that the effect of variables X1 and X2 on Y is positive so it is very likely that price perceptions and purchase intention will simultaneously influence purchasing decisions.